Fusion protein consisting of hemagglutinin small subunit and truncated nucleoprotein as a universal influenza vaccine candidate: Starting in-silico evaluation toward In Vitro expression - Fatemeh Morshedi; Elaheh Nazeri; Maryam Saleh; Behrokh Farahmand (Wolters Kluwer Medknow Publications, 2023)
Background: Influenza virus is a respiratory pathogen, which causes high degree of mortality and morbidity during seasonal epidemics and sporadic pandemics. By selecting conserved antigenic proteins, for example, hemagglutinin small subunit (HA2) and nucleoprotein (NP), we aimed to develop a vaccine based on a fusion protein leading to both cellular and humoral responses that are the most challenging aspects in designing a universal vaccine. Materials and Methods: The bioinformatics analysis was performed for HA2-NP structure and function prediction. Primers for the antigenic part of NP were designed using bioinformatics tools. The desired product was amplified via polymerase chain reaction using the designed primers, which was then penetrated into T vector, followed by insertion into pET28a vector in order to construct pET28a/NP. The pET28a/HA2, previously generated in our lab, was digested with the same restriction enzymes as pET28a/NP (HindIII/Xhol). Then, NP was inserted to the downstream region of HA2 to construct pET28a/HA2. Results: The generated pET28a/HA2-NP was transformed into Escherichia coli BL21 (DE3). The expression was induced by isopropyl β-d-l-thiogalactopyranoside. The results showed that the antigenic segment of NP was successfully cloned into pET28a/ HA2. The protein band of HA2-NP was observed on sodium dodecyl sulfate polyacrylamide gel electrophoresis, confirmed by Western blotting and purified with Ni-NTA purification system (QIAGEN, Germany). Conclusion: As currently available vaccines can cause some allergic reactions, using a chimer protein based on the bioinformatics analysis is continual, safe, and affordable, thus stimulating both cellular and humoral immunity systems. Our construct could potentially provide a basis for a universal vaccine candidate.